The babadook [videorecording (DVD)] - Kent, Jennifer (Film director); Davis, Essie; Henshall, Daniel, 1983-; Wiseman, Noah
Amelia is a single mother plagued by the violent death of her husband. When a disturbing storybook called Mister Babadook turns up at her house, she is forced to battle with her son's deep seated fear of a monster. Soon she discovers a sinister presence all around her.